Sistem Pendidikan Islam Pada Masa Daulah Abbasiyah - Nimatul Khoeriyah (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
The Abbasid Dynasty was a golden period in the history of Islamic civilization, especially in the fields of education and science. This study examines the Islamic education system that developed during that period, including institutional structures, teaching methodologies, and its contribution to the advancement of world civilization. Through a descriptive historical approach, this study reveals that the Abbasid education system was not only a model for the Islamic world, but also influenced the development of global education to this day.